Nova-like varible V603 Aquilae in 1999 - Baklanov, A. V.; Andronov, I. L.; Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
We perform the CCD (R) photometry of the nova-like variable V603 Aquilae (Nova Aquilae 1918) during 7 nights in 1999. The star showed quasi-periodic oscillations (QPO) with cycles ranging from 03035 to about 09055, and ”positive” superhumps with a photometric period of 014443? days. The ”A- scalegram” analysis shows evidence for QPOs with an effective period P : 17.6 minutes and an amplitude of 23 mmag.